PENGARUH PENGGUNAAN SILASE KULIT PISANG KEPOK (Musa paradisiaca formatypica) SEBAGAI PENGGANTI SEBAGIAN JAGUNG TERHADAP KARKAS DAN VISCERA BROILER - Salombre, Veny Joanet; Najoan, Marie; Sompie, Florencia N.; Imbar, Meity R. (Universitas Sam Ratulangi, 2018)
UTILIZATION OF ENSILAGE KEPOK BANANA PEELS REPLACING PART OF CORN IN THE DIET ON CARCASSES AND VISCERA INDICES OF BROILER. The purpose of the present research was to determine the substitution of corn with ensilage kepok banana peels (Musa paradisiaca formatypica) in the diet on carcasses and viscera indices of broiler. Trial was arranged using an experimental study. Sixty unsexed Cobb day old Chicks (DOC) were used in a Completely Randomized Design arrangement, with 4 treatments and 5 replications. Treatments were formulated as follow: R0 = 50% yellow corn + 0% ensilage kepok banana peels, R1 = 42,5% yellow corn + 7,5% ensilage kepok banana peels, R2 = 35% yellow corn + 15% ensilage kepok banana peels, R3 = 27,5% yellow corn + 22.5% ensilage kepok banana peels. Parameters measured were: carcass weight (g), abdominal fat (%), liver weight (%), and gizzard weight (%). Research results showed that, the subtitution of yellow corn with ensilage kepok banana peels gave a significant different (P<0,05) effect on carcass weight, abdominal fat percentage, liver weight percentage, and gizzard weight percentage. The higher the ensilage kepok banana peels replacing corn in the diets, the lower the carcass weight and abdominal fat percentage, whereas liver weight percentage and gizzard weight percentage both decreased as the subtitution of ensilage kepok banana peels increased. Carcass percentage was the only parameter that was not affected (P>0,05) by treatments. It can be concluded that the utilization of ensilage kepok banana peels up to 30% or 15% can still substitute yellow corn in broiler diets. Keywords : Broiler, Kepok Banana Peels, Carcasses, Viscera